Estrategias didácticas y la generación de ambientes de aprendizaje motivadores para potenciar el rendimiento académico de los estudiantes. Año Lectivo 2023 – 2024 - Correa Jiménez, Erin Dayana (2025)
Didactic strategies are essential to create learning environments that motivate students, which offers the possibility of promoting greater participation and interest in the subjects of study during the teaching-learning process, for the improvement of their academic performance. For the development of this work, the objective was: “To enhance the academic performance of students through the implementation of didactic strategies that generate motivating learning environments for the development of the teaching-learning process in the subject of Biology” The method used was inductive, based on direct observation of the teaching-learning process, which evidenced the few application of didactic strategies which generates a monotonous learning environment and consequently, the low academic performance of students, this led to the search for bibliographic material to solve the identified problem; the research approach is qualitative, focused on analyzing specific non-quantifiable characteristics of the educational environment. According to the nature of the information it is Participatory Action Research; an educational intervention proposal was implemented, with the active participation of both the students and the researcher, to improve the academic performance of the students. According to its temporality it is transversal, it was carried out during a relatively short period of time. The process began with the identification of the problem, then the review of bibliographic resources, elaboration and execution of the educational intervention proposal and the obtaining and analysis of results; the latter confirmed that the implementation of such strategies fostered a motivating learning environment and encouraged the students to develop study skills that enhanced their academic performance. It is concluded that the most significant didactic strategies with respect to the generation of motivating learning environments that enhance academic performance are: game-based learning, gamification, and simulation learning